Cooperative Script Learning Model as an Effort to Increase Interest and Learning Outcomes in Science - Utamaji Utamaji; Moh. Rifai (Jurnal Paradigma, 2025)
Social studies subjects in grade IV of SDN 2 Tanjunggunung face the problem of low interest and student learning outcomes. Students tend to be passive in learning because of the teacher-centered approach. This study applies the Cooperative Script learning model to overcome these problems. Classroom Action Research was conducted during the 2024/2025 semester involving 20 grade IV students. The implementation of the research uses two cycles, each consisting of planning, action, observation, and reflection. Data collection through observation, questionnaires, and tests. Data analysis used descriptive techniques with a percentage formula. In the first cycle, teacher activity reached 77.08%, student learning interest 70.75%, and learning outcomes 75.9%. Cycle II showed an increase in teacher activity of 100%, student learning interest of 84.25%, and learning outcomes of 85.1%. Students become more active in asking questions, confidently answering, and able to work well together. Cooperative Script is proven to be able to create a fun learning atmosphere and increase students' understanding of IPAS materials